2022
DOI: 10.1177/22808000221136369
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ZnO-doped magnesium phosphate cements on osteogenic differentiation of mBMSCs in vitro

Abstract: The insufficient osteogenesis of magnesium phosphate cements (MPCs) limits its further application. It is significant to develop a bioactive MPC with osteogenic properties. In this work, MPCs were reinforced by zinc oxide nanoparticles (ZnO-NPs). The composition, microstructure, setting time, compressive strength and degradation of ZnO-NPs/MPCs (ZNMPCs) were evaluated. The results showed that the setting times of MPCs were prolonged from 8.2 to 25.3 min (5.0ZNMPC). The exothermic temperatures were reduced from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…A similar effect—the strengthening of magnesium phosphate cement by doping with 1 wt.% of ZnO resulting in a mechanical strength of 49.2 MPa—is explained by the authors of Ref. [ 45 ]. The incorporated ZnO not only acted as stress concentration points absorbing a large amount of energy and promoting shear strain of the MPC matrix under the influence of external stress but also served as an effective barrier to dislocation movement, and efficiently impeded crack extension.…”
Section: Discussionsupporting
confidence: 65%
“…A similar effect—the strengthening of magnesium phosphate cement by doping with 1 wt.% of ZnO resulting in a mechanical strength of 49.2 MPa—is explained by the authors of Ref. [ 45 ]. The incorporated ZnO not only acted as stress concentration points absorbing a large amount of energy and promoting shear strain of the MPC matrix under the influence of external stress but also served as an effective barrier to dislocation movement, and efficiently impeded crack extension.…”
Section: Discussionsupporting
confidence: 65%
“…This suggests that the master transcription factor RUNX2 significantly regulates osteogenic differentiation of stem cells, and its expression tends to decrease over time, possibly because differentiated cells express more late-stage osteogenic markers. , A similar trend was observed in the literature, indicating that RUNX2 is responsible for the initial induction of osteodifferentiation and that the subsequent commencement of osteoblast maturation (COL1, OCN) results in lower levels of RUNX2 expression. It was observed that RUNX2 promoted ALP expression in GelMa–Al–Mn scaffolds significantly (Figure b). Collagen type 1 is a matrix maturation protein, which is an intermediate osteogenic marker secreted by differentiated stem cells Figure c depicts upregulated expression of the COL1 marker on day 21, which is significant for the GelMa–Al group.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen type 1 is a matrix maturation protein, which is an intermediate osteogenic marker secreted by differentiated stem cells. 26 Figure 6c depicts upregulated expression of the COL1 marker on day 21, which is significant for the GelMa−Al group. Expression of OCN was observed in Figure 6d, and significantly higher levels of OCN were found in hUMSCs of the day 21 GelMa−Al− Mn scaffold.…”
Section: Acs Applied Polymer Materialsmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies have found that ZnO-NP-enhanced MPCs exhibit characteristics such as prolonged setting time, reduced exothermic temperature, and increased compressive strength. Furthermore, co-culturing ZnO-NPs with murine bone marrow mesenchymal stem cells (mBMSCs) promotes the differentiation, proliferation, and mineralization capacity of mBMSCs and significantly increases the expression of osteogenic-related genes and proteins(Wang XM, Shi F, Zhao DC & Yan YG, 2022).…”
mentioning
confidence: 99%